Define Intervention: Opus Sectile (The Biblical archaeology review, 2022)
. A type of wall and floor decoration 2. A ritual of stamping sacred cakes 3. A type of crown worn by Byzantine emperors 4. A Roman dish of egg, leeks, and saffron 020 Answer: (1)